Sociospatial Ties and Postdisaster Reconstruction: An Analysis of the Assemblage in the Mega-Fire of Valparaíso - Castillo-Sepulveda, J (Wiley-Liss Inc., 2021)
Disasters affect sociospatial links in a dynamic and unstable meshwork of aspects that are reconfigured. In this sense, accounting for this complexity is central to analyze the transformation of the sociospatial linkage of the affected people and communities. Addressing from community environmental psychology, we propose the concept of assemblage to guide a situated reading of subjective, material, and community aspects present in a reconstruction process after a disaster. Following a qualitative methodology, using spatially referenced narrative interviews (n = 16) and thematic analysis, it is described how these links are presented in a community that lived the mega-fire of a part of the city of Valparaíso in Chile. The results describe that the experience of being a community is a variable flow within a process defined by an ever-emerging configuration of spatial, technological, personal, social, and sensory characteristics. We conclude by pointing out the qualities of the communities when considered from an assemblage perspective. © 2020 Wiley Periodicals LLC